EVALUATION OF PROXIMATE COMPOSITION AND SELECTED PHYSICO-CHEMICAL PROPERTIES OF BUTTERNUT SQUASH (CUCUBITA MOSCHATA) - Konadu, Mary; Assilidjoe, Enoch; Pedavoah, Mary; Quansah, Daniel (International Journal of Food Sciences, 2021)
Purpose: This study sought to evaluate of proximate composition and selected physico-chemical properties of butternut squash. Methodology: Samples were chosen randomly from Northern part Ghana specifically Kukobila and data analyzed statistically. Oil was extracted using soxhlet extraction method. Findings: Results showed that For the proximate analysis, fat content of the pulp was 1.16% and carbohydrate 72.70%. The fibre content of the defatted seed residue was 5.59%, ash (6.86%) and protein (49.20%). The acid value, saponification value, iodine value, peroxide value and free fatty acid were 3.42mgKOH/g, 15.43mgKOH/g, 21.08gI2/100g, 2.50meqO2/kg and 1.71 respectively. The high oil content of the seeds coupled with fairly low acid value makes it suitable as edible oil, a food supplement and suggest its suitability for the production of paints, inks but not suitable for soap and biodiesel production Unique contribution to theory, practice and policy: Farmers should avoid local consumption of butternut squash due to lack of knowledge on the potentials and uses; since its underutilized and cultivated mainly for export. More research should be carried out to convert Butternut squash into breakfast meals and baby feeds due to its high protein content and gluten free nature